Pengembangan Keberbakatan dan Minat Siswa dalam Konteks Pendidikan - Habsy, Bakhrudin All; Lena, Annora Malva; Aryanti, Dwi Wulan; Asfinda, Hany (Lembaga Yasin AlSys, 2024)
The analysis that we make this time aims to develop students' giftedness, which the term gifted itself can be described by Plato as Men of gold or